Development of the Bentbol Game toward Physical Education Learning at Elementary School - Rizki Praditya Pangestu; Agus Pujianto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Physical education learning in elementary schools tends to be monotonous, less engaging, and limited by inadequate facilities, which affects students’ interest and participation. This study aimed to develop the Bentbol (Ball Fortress) game model as an innova tive PJOK learning alternative suitable for elementary school students. The study used the Research and Development (R&D) method with the ADDIE model, con sisting of analysis, design, development, implementation, and evaluation stages. The subjects were fourth-grade students at SD Negeri 1 Rancamaya, SD Negeri 1 Gunung Lurah, and SD Negeri 3 Cilongok. Data were collected through observa-tion, interviews, and questionnaires, then analyzed using descriptive quantitative and qualitative techniques. The results showed that the Bentbol game model achieved an expert validation score of 95% in the very feasible category. Small-scale trials obtained 77.53% in the good category, while large-scale trials reached 90.06% in the very good category. The improvement in these results shows that the Bentbol game model is effective in increasing students' activeness, coopera-tion, and movement skills. Therefore, the Bentbol game model is feasible and effective as an innovative and enjoyable PJOK learning alternative in elementary schools.